2020
DOI: 10.1371/journal.pone.0227411
|View full text |Cite
|
Sign up to set email alerts
|

The gene encoding the ketogenic enzyme HMGCS2 displays a unique expression during gonad development in mice

Abstract: Disorders/differences of sex development (DSD) cause profound psychological and reproductive consequences for the affected individuals, however, most are still unexplained at the molecular level. Here, we present a novel gene, 3-hydroxy-3-methylglutaryl coenzyme A synthase 2 (HMGCS2), encoding a metabolic enzyme in the liver important for energy production from fatty acids, that shows an unusual expression pattern in developing fetal mouse gonads. Shortly after gonadal sex determination it is up-regulated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…4 B ). These included the ketogenic gene Hmgcs2 ( 70 ), the hydroxysteroid dehydrogenase gene Ark1c14 ( 71 ), and multiple others ( Fig. 4 B ).…”
Section: Resultsmentioning
confidence: 99%
“…4 B ). These included the ketogenic gene Hmgcs2 ( 70 ), the hydroxysteroid dehydrogenase gene Ark1c14 ( 71 ), and multiple others ( Fig. 4 B ).…”
Section: Resultsmentioning
confidence: 99%
“…5 a, Agt (angiotensinogen) was expressed in ALCs but not in Sertoli or germ cells in adult testes. Enriched expression in ALCs has previously been observed for Hmgcs2 (3-hydroxy-3-methylglutaryl-CoA synthase 2) 35 , 36 , Lcn2 (lipocalin-2) 37 , and Sepp1 (selenoprotein P, plasma, 1) 38 . A high level of Ptgds (prostaglandin D2 synthase) expression was detected in ALCs, although the expression was also detected in Sertoli cells from some, but not all, testicular tubules 39 .…”
Section: Resultsmentioning
confidence: 65%
“…We detected the missense mutation c.1502G > A/p.R501Q in Patient 6 in the compound heterozygous state, and a previous study has reported a Chinese case in the homozygous state (Ma and Yu, 2018). Previous reports have also suggested that arginine at position 501 is critical to enzymatic function (Bagheri-Fam et al, 2020). Moreover, variation in amino acids in the same position, c.1502G > C/p.R501P, has also been found in two Thai patients (Rojnueangnit et al, 2020).…”
Section: Discussionmentioning
confidence: 96%